Analysis of Consumer Satisfaction Levels on the Value of Sagoku Products From Sago Meambo Food, Mata output, Kendari District. - La Ode Muhammad Arif; La Rianda; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
This study aims to study the process of sago processing at the Meambo Food Sago Business in the Mata Village, Kendari District, Kendari City, to determine the product development process using the Quality Function Deployment (QFD) method on sago processing at the Meambo Food Sago Business in the Mata Village, Kendari District, Kendari City.